2022
DOI: 10.1038/s10038-022-01081-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive targeted next-generation sequencing in patients with slow-flow vascular malformations

Abstract: Recent studies have shown that the PI3K signaling pathway plays an important role in the pathogenesis of slow-ow vascular malformations (SFVMs). Analysis of genetic mutations has advanced our understanding of the mechanisms involved in SFVM pathogenesis and may identify new therapeutic targets. We screened for somatic variants in a cohort of patients with SFVMs using targeted next-generation sequencing. Targeted next-generation sequencing of 29 candidate genes associated with vascular anomalies or with the PI3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Complex and syndromic VMs often result from mosaicism in early developmental stages and can vary in manifestation depending on the timing of the mutation and the cell lineage affected [190,202]. Despite these differences, all GOF PIK3CA-associated VMs share the same pathogenesis as slow-flow VMs (SFVMs), which are frequently caused by GOF PIK3CA mutations [18,190,203]. This has been supported by recent sequencing data in patients with slow-flow VMs [18].…”
Section: Somatic Gof Pik3ca Mutations Are Genetic Drivers For Vascula...mentioning
confidence: 80%
See 1 more Smart Citation
“…Complex and syndromic VMs often result from mosaicism in early developmental stages and can vary in manifestation depending on the timing of the mutation and the cell lineage affected [190,202]. Despite these differences, all GOF PIK3CA-associated VMs share the same pathogenesis as slow-flow VMs (SFVMs), which are frequently caused by GOF PIK3CA mutations [18,190,203]. This has been supported by recent sequencing data in patients with slow-flow VMs [18].…”
Section: Somatic Gof Pik3ca Mutations Are Genetic Drivers For Vascula...mentioning
confidence: 80%
“…The transforming potential of PI3K catalytic isoforms was realized decades ago in cancer research [6][7][8], and these isoforms have been defined as oncogenes [8,9]. Somatic GOF PIK3CA point mutations have been frequently described in various cancers as an oncogene [10][11][12][13][14][15], as well as in many forms of vascular anomalies, especially the well-known vascular malformations (VMs) [16][17][18][19][20]. This shared genetic similarity between tumors and vascular anomalies suggests that as benign tumors, VeMs might have similar genetic underpins as cancers caused by the exact same somatic PIK3CA GOF mutations [16,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Part I had a hybrid study design consisting of a placebocontrolled study to evaluate safety, tolerability, and PK of ART-001 in SRD (steps [1][2][3][4][5] and an open-label study to evaluate the food effect (step 6). Part I was conducted by the alternating panel with groups A and B (8 subjects per group).…”
Section: Part I: Srd Studymentioning
confidence: 99%
“…1,2 Multiple studies demonstrated that most of the patients with SFVMs have somatic gain-of-function mutations in genes encoding PI3Kα and its upstream or downstream kinases. [3][4][5][6][7] In addition, there is accumulating clinical evidence suggesting the pharmacological inhibition of PI3K/AKT/mTOR pathway (i.e., mTOR inhibitor sirolimus and PI3Kα inhibitor alpelisib) would be a promising approach for the treatment of SFVMs. [8][9][10][11][12] ART-001 (serabelisib, also known as TAK-117) is a novel, orally available, selective PI3Kα inhibitor, originally developed for advanced solid tumors, but is now being developed for the treatment of SFVMs in both the pediatric and adult populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation